Application of Fuzzy Logic in Visual Novel Evaluation System Using Unity 3D - Epafraditus Memoriano; Riza Arifudin (Universitas Negeri Semarang, 2025)
Purpose: Visual novels, narrative-driven games focused on character interaction, commonly employ point-based evaluation systems that struggle to represent the inherent complexity and uncertainty of player choices. This research introduces a novel approach: integrating fuzzy logic into visual novel evaluation systems using Unity 3D. Fuzzy logic addresses the limitations of point-based systems by accounting for the